Pharmacists’ Awareness and Perceptions of Biosimilars in Saudi Arabia - Iqbal, Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: The current study aimed to evaluate practicing pharmacists’ awareness and perceptions about biosimilars in Saudi Arabia. Materials and Methods: A cross-sectional study was performed using a prevalidated and self-administered research tool by convenience sampling method. Registered pharmacists were approached to participate in the study. Descriptive and inferential statistics were performed using the Statistical Package for the Social Sciences version 24.0. P < 0.05 was considered statistically significant. Results: Out of 319 pharmacists, 34.79% were familiar and 12.87% were very much familiar with the biosimilars. Around 33.22% were aware of the approval pathway and regulatory issues associated with prescribing biosimilars. The majority of the respondents (>60%) had good awareness and positive perception toward biosimilars. Conclusion: This study concluded an appropriate awareness and positive perception toward biosimilars among pharmacists in Saudi Arabia. Statistically non-significant association regarding biosimilars’ perception and awareness was observed between male and female pharmacists.